Multimodal Imaging of Lamellar Macular Holes. (31st January 2021) - dell'Omo, Roberto; Filippelli, Mariaelena; De Turris, Serena; Govetto, Andrea; Napolitano, Pasquale; Ermanno dell'Omo,; Costagliola, Ciro
Abstract : Evolution of imaging techniques has renewed interest in the diagnosis of lamellar macular hole (LMH) and greatly implemented the possibilities of gaining more detailed insights into its pathogenesis. Among noninvasive techniques, optical coherence tomography (OCT) is considered the primary examination modality to study LMHs, given its ability to image foveal structure and its widespread availability. OCT also allows to resolve the epiretinal materials associated with LMH, i.e., tractional epiretinal membranes (ERMs) and epiretinal proliferation (EP). En face OCT reconstructions are useful to confirm the foveal abnormalities shown by the eyes with LMH, whereas OCT angiography may reveal alterations of the size and shape of the foveal avascular zone and alterations of the density of the superficial and deep vascular plexuses. On slit-lamp biomicroscopy or fundus camera examination, LMH appears as a round or oval, reddish lesion at the center of the macula, slightly darker than the surrounding retina. The associated tractional ERM, causing wrinkling and glistening of the retinal surface, is usually readily appreciable, whereas EP is hardly apparent on biomicroscopy or fundus photography since the retina surface appears smooth. When imaged with blue fundus autofluorescence (B-FAF) imaging, LMHs are characterized by an increased autofluorescent signal, the intensity of which does not correlate with the thickness of the residual outer retinal tissue. Green reflectance and blue reflectance (BR) images clearly show the increased reflection and wrinkling of the retinal surface caused by tractional ERM associated with LMH. BR and multicolor imaging enable the visualization of EP associated with LMH in the form of a sharply demarcated dark area and in the form of a yellowish area surrounding the hole, respectively. Scarce data regarding invasive imaging techniques, such as fluorescein angiography, for the study of LMH are available in the literature. The aim of this review is to evaluate the contribution that each imaging modality can provide to study the morphologic characteristics of LMH.